KERJASAMA INDUSTRI PERTAHANAN INDONESIA-KOREA SELATAN DALAM UPAYA MENINGKATKAN PERTAHANAN MARITIM INDONESIA - Putri Amelinda Dhurroh, (2022)
The defense equipment that has been produced by Indonesia through the cooperation of the two countries, namely the Submarine. Submarines are important defense equipment that must be owned by Indonesia, considering the large area of Indonesian waters, submarines can be used to monitor Indonesian territorial and provide a deterrent effect on opponents. With the right spot and covert, the submarine is able to attack the enemy quickly without being detected. A long-range conventional submarine unit can contribute greatly to global interests and can make Indonesia a leader in the regional area, in assisting the concept of the Indonesian Navy in the present, that is making Indonesia's maritime defense to an international standard. Maritime defense systems, especially in archipelagic countries, certainly need a strong Navy synergy with a compatible Air Force, therefore the capability of air space by air power is very much needed to create a reliable sea power. Therefore, the development of fighter aircraft by Indonesia and South Korea is an important part of Indonesia's attempts to achieve Sea Power because there are several Air Force capabilities that immensely contribute to maritime defense.